Islam dan Peran Politik Wanita: Diskursus antara Marginalisasi dan Pengakuan - Fikri, Sariatul (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
The discourse on the political role of women in Islam is one of the most complex and debated issues in the context of gender equality and religious interpretation. The idea that women have a subordinate position is deeply embedded not only in the minds of men but also in women themselves. This is due to the strong and pervasive patriarchal construction, which emphasizes male superiority and is supported by various institutions such as the state, religion, and culture. This study aims to examine the arguments in the discourse on the political role of women in Islam, trace the roots of marginalization, and efforts to recognize the role of women in politics. This study uses a descriptive qualitative research method with a type of library research, namely reference sources from journal articles, books, and other literature that are relevant to the research theme. The results of the study show that conservative interpretations of religious texts are often used to marginalize the political role of women, associate political leadership with the male realm and emphasize women's domestic roles. This approach is supported by patriarchal cultural and social norms, which have long dominated many Muslim societies.